National trends and regional variation in immediate breast reconstruction rates. Issue 9 (21st June 2016) - Jeevan, R.; Mennie, J. C.; Mohanna, P. N.; O'Donoghue, J. M.; Rainsbury, R. M.; Cromwell, D. A.
Abstract: Background: Previous studies have identified variation in immediate reconstruction (IR) rates following mastectomy for breast cancer across English regions during a period of service reorganization, a national audit and changing guidelines. This study analysed current variations in regional rates of IR in England. Methods: Patient‐level data from Hospital Episode Statistics were used to define a cohort of women who underwent primary mastectomy for invasive or in situ breast carcinoma in English National Health Service (NHS) hospitals between April 2000 and March 2014. A time series of IR rates was calculated nationally and within regions in 28 cancer networks. Regional IR rates before and after the national audit were compared, using logistic regression to adjust for patient demographics, tumour type, co‐morbidity and year of mastectomy. Results: Between 2000 and 2014, a total of 167 343 women had a mastectomy. The national IR rate was stable at around 10 per cent until 2005; it then increased to 23·3 per cent by 2013–2014. Preaudit (before January 2008), adjusted cancer network‐level IR rates ranged from 4·3 to 22·6 per cent. Postaudit (after April 2009) adjusted IR rates ranged from 13·1 to 36·7 per cent, with 20 networks having IR rates between 15 and 24 per cent. The degree of change was not greatest amongst those that started with the lowest IR rates, with four networks with the largest absolute increase also starting with relatively high IR rates. Conclusion: The national IR rate increased throughout the study period. Substantial regional variation remains, although considerable time has elapsed since a period of service reorganization, guideline revision and a national audit. Abstract : Immediate reconstruction on the rise